The Relationship between Students' Perceptions of Parenting Styles and their University Life Adjustment - Said Aldhafri (Sultan Qaboos University, 2016)
The current study examines the association between university students' perceptions of parenting styles and their university life adjustment. Data were collected from Sultan Qaboos University (SQU) in Oman. The sample consisted of 2562 undergraduate students (59% were females) from different colleges and study years. The participants responded to two questionnaires. The first questionnaire examined students' perceptions of three parenting styles: authoritative (7 items), authoritarian (7 items), and permissive (6 items). The university life adjustment was examined by a questionnaire that focused on psychological (10 items) and non-psychological (5 items) problems that students face during university years. Both measures were found to be stable and reliable. The findings showed that college students reported high levels of authoritative and authoritarian parenting styles, low levels of permissive style, and low psychological and non-psychological problems. Additionally, results of two separate re- gression analyses indicated that students' psychological problems were predicted positively by authori- tarian mother and negatively by authoritative mother and authoritative father; the non-psychological problems were predicted negatively by authoritative father and positively by authoritarian mother and permissive father. Findings were discussed within Omani cultural context.